2013
DOI: 10.1007/s10663-013-9241-z
|View full text |Cite
|
Sign up to set email alerts
|

Logistics performance and export competitiveness: European experience

Abstract: This article aims to analyse the importance of logistics performance in European Union (EU) exports over a sample period in order to detect possible advances on behalf of Member States. We will estimate several gravity equations using the Logistics Performance Index (LPI) and its components as characteristic proxy variables of trade facilitation. In order to avoid the possible heterogeneity caused by sample bias, we will employ the two-stage model proposed by Heckman. The estimations of the gravity models usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 13 publications
6
74
1
2
Order By: Relevance
“…Besides the economic factors, there are many semi-economic and political factors playing important roles in determining trade flow. Many researchers augmented the simple gravity model with these factors as control variables or dummy variables, such as sharing the same border and having the same language or colonial heritage [4][5][6]. In this study, the standard gravity model is augmented with these semi-economic and political variables.…”
Section: Methodological Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the economic factors, there are many semi-economic and political factors playing important roles in determining trade flow. Many researchers augmented the simple gravity model with these factors as control variables or dummy variables, such as sharing the same border and having the same language or colonial heritage [4][5][6]. In this study, the standard gravity model is augmented with these semi-economic and political variables.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…Marti et al [6] analyzed the impact of LPI and its components on trade flow in developing countries; the results revealed that LPI and all of its components have a significant positive effect on trade flows in all of the regions. Puertas et al [5] examined the effect of LPI and its components on export in European Union (EU, Brussels, Belgium) and found that LPI and all of its components have a significant positive effect on export. Chakraborty and Mukherjee [34] researched the influence of LPI on export orientation and found that LPI has a significant positive impact on trade orientation.…”
Section: Logistics Performance and International Tradementioning
confidence: 99%
“…On a different note, researchers have also attempted to ascertain the importance of the components of the LPI with regard to trade, either by including several components in the same model (Felipe and Kumar, 2012) or by estimating regressions that consider only one of the components (Hertel and Mirza, 2009;Puertas et al, 2013). Both papers conclude that infrastructure is the most important component in comparison to customs efficiency 1 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The policies have helped to keep EU freight moving quickly. Evidence shows that EU logistics performance has become a decisive factor in export competitiveness (Puertas et al 2014).…”
Section: Recommendations For Improving Harmonisation In Logistics Sermentioning
confidence: 99%